2019
DOI: 10.1002/cncy.22126
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cytocentrifugation supernatant fluid and formalin‐fixed paraffin‐embedded tissue for targeted next‐generation sequencing

Abstract: BACKGROUND:The emergence of less invasive procedures coupled with the growth of molecular testing have created a need for clinical laboratories to optimize workflows to enable tissue preservation and ancillary testing. In the preparation of formalin-fixed paraffin-embedded cell blocks (FFPE CBs), there is a cytocentrifugation step for cell pellet extraction that results in postcentrifugation supernatant fluid (SN). This SN, which in most routine workflows is discarded, has been suggested to contain adequate ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 32 publications
0
23
2
Order By: Relevance
“…No further quality measures were used. 9 The CB FFPE sample and direct smears are used for diagnosis. The final report included a statement indicating F I G U R E 1 A, Flowchart of the old workflow using formalin fixed paraffin embedded cell blocks (FFPE CB).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…No further quality measures were used. 9 The CB FFPE sample and direct smears are used for diagnosis. The final report included a statement indicating F I G U R E 1 A, Flowchart of the old workflow using formalin fixed paraffin embedded cell blocks (FFPE CB).…”
Section: Methodsmentioning
confidence: 99%
“…Then NGS is ordered through EMR, and subsequent nucleic acid extraction and NGS analysis are performed [Color figure can be viewed at wileyonlinelibrary.com] on both workflows were performed as previously described. 9 Information for TAT and sample quality metrics were retrieved from pathology LIMS systems. The cost savings associated with the new workflow were calculated based on hourly wages of staff involved in the by-passed steps with new workflow.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported on the promising role of NSCLC FNA supernatant fluid samples for genomic profiling. [53][54][55] When compared with the mutation profile obtained from plasma ctDNA, the FNA supernatant fluid specimens were able to identify additional genomic alterations with therapeutic targets and detect mutations with higher allele fractions. 54 This increases the potential for the better use of limited-volume FNA specimens, especially in situations in which the diagnostic yield is adequate for a diagnosis of NSCLC but the cellular component is borderline or inadequate for lung cancer biomarker testing.…”
Section: Pleural Effusion and Ascitic Fluidmentioning
confidence: 99%
“…The advantage of using FNA supernatant fluid for mutational profiling in conjunction with immunohistochemistry and fluorescence in situ hybridization-based testing using conventional substrates such as cell blocks and/or liquid-based cytology is a more efficient and faster turnaround time for obtaining biomarker test results in these patients with NSCLC. 55 The ability to incorporate FNA supernatant fluid specimens into the clinical molecular workflow provides an opportunity to provide clinically relevant genomic information without the need for a repeat biopsy in patients for whom the tissue biopsy was insufficient.…”
Section: Pleural Effusion and Ascitic Fluidmentioning
confidence: 99%